Examining Types of Audit Judgment and Objectivity Threat: Empirical Findings from Public and Private Sector Internal Auditors in Malaysia - Fazlida Mohd Razali (Indonesian Journal of Economics, Social, and Humanities, 2020)
Increasing number of litigation suits against internal auditors has proved that there is heightened scrutiny on the quality of internal auditor’s judgment. As internal auditor’s judgment relies highly upon by the stakeholders, this paper aims to identify the types of audit judgment deemed to be critical for the success of an audit engagement. It also explores the types of objectivity threat experienced by Malaysian internal auditor. The present study also examined if there had been significant difference between objectivity threat experienced by public sector internal auditors and those of the private sector. The paper opted for an exploratory study using the questionnaires. A total of 150 copies of questionnaire were distributed to internal auditors working in private and public sectors. The findings indicated risk judgment (judgment on existing and emerging risk faced by organisation) as the most critical success factor in internal audit engagement. The findings also revealed that social pressure, cognitive biases, and intimidation as the top three threats that could threaten internal auditor objectivity, thus possibly affect internal auditor ability to make an objective judgment. However, this study found that there was no significant differences between the objectivity threats experienced by internal auditors in the private sector and those in the public sector. The research extent internal auditing literatures which focuses on the factors influencing internal auditor’s objectivity, but tended to omit the impact of the objectivity on influencing internal auditor’s judgment. This study has provided evidence of potentially serious risk of objectivity threats that may impair the internal auditors’ objectivity, thus reducing their ability to make an objective judgment. This paper fulfils an identified need to study flaws in internal auditor’s judgment and the existences of objectivity threat in Malaysian internal audit environment regardless either in public or private sector.Increasing number of litigation suits against internal auditors has proved that there is heightened scrutiny on the quality of internal auditor’s judgment. As internal auditor’s judgment relies highly upon by the stakeholders, this paper aims to identify the types of audit judgment deemed to be critical for the success of an audit engagement. It also explores the types of objectivity threat experienced by Malaysian internal auditor. The present study also examined if there had been significant difference between objectivity threat experienced by public sector internal auditors and those of the private sector. The paper opted for an exploratory study using the questionnaires. A total of 150 copies of questionnaire were distributed to internal auditors working in private and public sectors. The findings indicated risk judgment (judgment on existing and emerging risk faced by organisation) as the most critical success factor in internal audit engagement. The findings also revealed that social pressure, cognitive biases, and intimidation as the top three threats that could threaten internal auditor objectivity, thus possibly affect internal auditor ability to make an objective judgment. However, this study found that there was no significant differences between the objectivity threats experienced by internal auditors in the private sector and those in the public sector. The research extent internal auditing literatures which focuses on the factors influencing internal auditor’s objectivity, but tended to omit the impact of the objectivity on influencing internal auditor’s judgment. This study has provided evidence of potentially serious risk of objectivity threats that may impair the internal auditors’ objectivity, thus reducing their ability to make an objective judgment. This paper fulfils an identified need to study flaws in internal auditor’s judgment and the existences of objectivity threat in Malaysian internal audit environment regardless either in public or private sector.